Effets et enjeux de l’interdisciplinarité en sociolinguistique. D’une approche discursive à une conception praxéologique des représentations linguistiques - Petitjean, Cécile (My University, 2011)
This article shows how the notion of social representation acts as a catalyst for interdisciplinary relations between sociolinguistics and both language sciences and all other fields of social sciences. The theoretical and methodological problems posed by the study of social representations show that interdisciplinary discussion may be a necessity and not only a scientific choice. We show how interdisciplinary exchanges have influenced the methodological and analytical framework used in the sociolinguistic study of social representations, and how these protocols have revealed in turn the limitations of the definition of the notion and, finally, led to a reorientation of the initial methodologies. We will illustrate the results of these interdisciplinary intertwining in practical terms, by proposing a new approach to social representations (i.e. the representation-in-action) that was inspired by different fields of language and social sciences. We will analyze the representations of interactional competences built by actors of didactic interactions, which allows us to show the relevance of a praxeologic conception of social representations.